2018
DOI: 10.1021/acs.langmuir.8b00172
|View full text |Cite
|
Sign up to set email alerts
|

Directional Transport of a Liquid Drop between Parallel–Nonparallel Combinative Plates

Abstract: Liquids confined between two parallel plates can perform the function of transmission, support, or lubrication in many practical applications, due to which to maintain liquids stable within their working area is very important. However, instabilities may lead to the formation of leaking drops outside the bulk liquid, thus it is necessary to transport the detached drops back without overstepping the working area and causing destructive leakage to the system. In this study, we report a novel and facile method to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Finally, an optimized ratchet cycle was carried out to verify our analysis. Compared with previous studies, 25,30,31,37,38 the present strategy provides the following new advances.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Finally, an optimized ratchet cycle was carried out to verify our analysis. Compared with previous studies, 25,30,31,37,38 the present strategy provides the following new advances.…”
Section: Discussionmentioning
confidence: 86%
“…This phenomenon has been speculated to be mainly caused by the asymmetric depinning (AD) of droplets, which means that the trailing edge remains pinned as the leading edge advances during the squeezing process and that the leading edge remains pinned as the trailing edge recedes during the relaxing process. 28,[30][31][32][33] Later research found that the droplet is transported not only by the AD but also by symmetric depinning (SD), which means that both the leading and trailing edges are advancing or receding. 31 In fact, the efficiency of the SD model is much lower than that of the AD model.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be achieved by creating a wettability gradient through chemical or thermal treatment, [ 22–25 ] roughness gradient through varying the spacial roughness ratio, [ 8,26–30 ] or surface structural gradient. [ 2,3,31–37 ] It has also been shown that spontaneous motion can be achieved between nonparallel [ 38–40 ] or flexible plates. [ 41 ] Besides, Chen et al [ 42 ] demonstrated the continuous unidirectional liquid spreading on the peristome surface of Nepenthes alata , which inspired many surface designs for liquid transport.…”
Section: Introductionmentioning
confidence: 99%